Application of Core Processes for Understanding Multiple Concurrent Sexual Partnerships Among Adolescents in Uganda - Nalukwago, Judith; Alaii, Jane; Borne, Bart Van Den; Bukuluki, Paul Mukisa; Crutzen, Rik (Frontiers in Public Health, 2018)
Introduction: Adolescents in Uganda, as in other sub-Saharan countries, engage in sex with multiple concurrent partners, thus placing them at risk for HIV and unplanned pregnancies, but it is not clear why. This study explored why adolescents in Uganda engage in multiple concurrent sexual partnerships (MCSP). Methods: This study used a Core Processes methodology. We used the processes of brainstorming, and identification of evidence and theoretical support, in various phases/steps of intervention planning, to provide possible explanations for adolescent MCSP. Results: Adolescents were found to have limited knowledge of the risks associated with MCSP and perceived a low risk for HIV. Peer influence to engage in MCSP exacerbated the problem among adolescents. Poor communication with sexual partners and parents and societal indifference to multiple sexual partnerships increased permissive attitudes toward infidelity. The unclear adolescent sexual and reproductive health policies hampered access to services, and transactional sexual relationships with older (polygamous) sexual partners increased the HIV risk. Adolescents were found to be more concerned about unplanned pregnancies than HIV risk. Discussion: From the empirical evidence, adolescent health programs in Uganda should incorporate comprehensive sexual health education on HIV and teenage pregnancy risk-reduction strategies. Programs should strengthen parental and community support through enhanced collaborative training on communication with and for adolescents. Forming strategic partnerships with various stakeholders for concerted efforts to address the MCSP problem among adolescents is critical.